First record of Brachycoris Stål (Hemiptera: Heteroptera: Pentatomidae) in India, with description of a new species - Salini, S (Zootaxa, 2017)
The genus Brachycoris remained monotypic so far, with Brachycoris semiflavus Stål, 1871 from Philippines. In this paper, the genus is redescribed and its distribution expanded with the description of Brachycoris tralucidus sp. nov., based on specimens from southern part of India. B. tralucidus sp. nov. is described and illustrated based on male and female genitalia.